Kekuatan Budaya Lokal: Menjelajahi 3S (Sipakatau, Sipakalebbi, dan Sipakainge’) sebagai Simbol Kearifan Lokal - Nur, Rezky Juniarsih; Wildan, Dadan; Komariah, Siti (MIMESIS, 2023)
Local wisdom is an important cultural heritage for a society in maintaining its cultural identity. One of these is the Sipakatau, Sipakalebbi, and Sipakainge culture, which consists of three indigenous wisdom ideas that are crucial to the way of life of the Makassar tribal people. This study employs a literature review research method for examining, analyzing, and synthesizing the body of previous literature on a given research issue. The literature review approach will be employed in this study to analyze the connections between sociology learning initiatives, including character development, and the Sipakatau, Sipakalebbi, and Sipakainge's local knowledge. Researchers have reviewed a total of 33 journals related to livelihood keywords such as "local wisdom 3S culture (Sipakatau, Sipakalebbi, and Sipakainge'), "character learning projects," "sociological learning," and other relevant combinations of keywords. Internalization of values Bugis-Makassar cultural values ​​in sociology learning can be linked to the learning project profile, which focuses on developing student character through learning more contextually and integrated with everyday life.